Solve this


$6 x^{2}+11 x+3=0$



Given :

$6 x^{2}+11 x+3=0$

$\Rightarrow 6 x^{2}+9 x+2 x+3=0$

$\Rightarrow 3 x(2 x+3)+1(2 x+3)=0$

$\Rightarrow(3 x+1)(2 x+3)=0$

$\Rightarrow 3 x+1=0$ or $2 x+3=0$

$\Rightarrow x=\frac{-1}{3}$ or $x=\frac{-3}{2}$

Hence, $\frac{-1}{3}$ and $\frac{-3}{2}$ are the roots of the equation $6 x^{2}+11 x+3=0$.


Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now